Longitudinal evaluation of iron concentration and atrophy in the dentate nuclei in friedreich ataxia. Issue 3 (9th January 2019) - Ward, Phillip G. D.; Harding, Ian H.; Close, Thomas G.; Corben, Louise A.; Delatycki, Martin B.; Storey, Elsdon; Georgiou‐Karistianis, Nellie; Egan, Gary F.
Abstract: Background: Friedreich ataxia is a recessively inherited, progressive neurological disease characterized by impaired mitochondrial iron metabolism. The dentate nuclei of the cerebellum are characteristic sites of neurodegeneration in the disease, but little is known of the longitudinal progression of abnormalities in these structures. Methods: Using in vivo magnetic resonance imaging, including quantitative susceptibility mapping, we investigated changes in iron concentration and volume in the dentate nuclei in individuals with Friedreich ataxia (n = 20) and healthy controls (n = 18) over a 2‐year period. Results: The longitudinal rate of iron concentration was significantly elevated bilaterally in participants with Friedreich ataxia relative to healthy controls. Atrophy rates did not differ significantly between groups. Change in iron concentration and atrophy both correlated with baseline disease severity or duration, indicating sensitivity of these measures to disease stage. Specifically, atrophy was maximal in individuals early in the disease course, whereas the rate of iron concentration increased with disease progression. Conclusions: Progressive dentate nucleus abnormalities are evident in vivo in Friedreich ataxia, and the rates of change of iron concentration and atrophy in these structures are sensitive to the disease stage. The findings are consistent with an increased rate of iron concentration and atrophy early in the disease, followed by iron accumulation and stable volume in later stages. This pattern suggests that iron dysregulation persists after loss of the vulnerable neurons in the dentate. The significant changes observed over a 2‐year period highlight the utility of quantitative susceptibility mapping as a longitudinal biomarker and staging tool. © 2019 International Parkinson and Movement Disorder Society